PENGARUH KONSUMSI SUSU KEDELAI TERHADAP KOLESTEROL TOTAL PADA PENDERITA HIPERKOLESTEROLEMIA DI WILAYAH KERJA PUSKESMAS LUBUK BUAYA PADANG - Andika, Mira (Menara Ilmu, 2019)
Hypercholesterolemia is a state of increasing blood cholesterol levels that can increase therisk of coronary heart disease due to blockage by cholesterol plaques. Soy milk containsIsoflavones and Leshitin which can bind and excrete excess cholesterol in the blood. The purposeof this study was to determine the effect of consumption of soy milk on total blood cholesterol inpatients with hypercholesterolemia in the Puskesmas Lubuk Buaya working area .The study was pre-experimental, with one group pretest-posttest design. Data was collectedon 17 June - 1 July 2018 at the home of each respondent. The number of subjec were 10 persons.Sampling done by purposive sampling. Data was taken through patient data observation sheets.The analysis used in the study is a paired sample t-test.The results showed that the average blood cholesterol before consumption of soy milk was219.80 mg / dl and the average blood cholesterol after consumption of soy milk was 213.50 mg /dL. Total blood cholesterol after consumption of soy milk decreased by 6.3 mg / dl. After the pairedt-test statistical test was obtained p value = 0.004 (p <0.05), This shows that there was astatistically significant influence on consumption of soy milk even though clinically it has nosignificant effect but consumption of soy milk continues to influence the decrease in total bloodcholesterol.Based on the results of this study it can be concluded that soy milk has an effect on totalblood cholesterol in patients with hypercholesterolemia.. It expected that this soy milk healthworker can be used as an alternative treatment for hypercholesterolemia..Keywords : Hypercholesterolemia, Soy Milk, Total Blood Cholesterol